A CLINICAL-RADIOGRAPHIC EVALUATION OF CROWN AND NON-METAL POST RESTORATION AFTER ROOT CANAL TREATMENT USING MODIFIED STRINDBERG CRITERIA IN ACADEMIC DENTAL HOSPITAL YOGYAKARTA - Erma Sofiani; Jihan Nadhirah Natasya (ODONTO : Dental Journal, 2022)
Background: Root canal treatment failure can be caused by periapical lesions and inadequate restorations such as post restorations. It showed that comprehensive evaluation, such as clinical or radiographic evaluation, is needed to observe the healing of endodontically treated dental and intra-radicular post-condition, especially fiber post and fiber reinforced composite (FRC). This research aims to evaluate the clinical and radiographic success of endodontically treated teeth restored with single crown restoration using a non-metal post. Methods: This study is a cross-sectional design and descriptive observation of evaluating endodontically treated teeth. 72 samples were collected from medical records, and radiographs of endodontically treated patients; then, scoring was carried out to categorize the treatment outcome using modified Strindberg criteria. Results: Endodontically treated dental restoration with non-metal post evaluation showed 63,9% teeth categorized as uncertain, followed by 36,1% teeth categorized as success and 0% in the failure category. Conclusion: The result of this study suggests that a longer follow-up period will be needed to achieve a more stable evaluation result.